Remote methods of estimating carbon reserves at the site of the Far Eastern carbon polygon - Kostyk, Veronika; Yaroslavtsev, Alex; Lialiushko, Evgeny; Nagornyi, Konstantin; Vikhrenko, Snezhana; Lisina, Irina; Belenev, Sergey (Edelweiss Applied Science and Technology, 2025)
Carbon test sites are test sites located in unique ecosystems where technologies for measuring, monitoring and controlling greenhouse gases are developed and tested. The paper considers the Far East Carboniferous Polygon (FECP) site located in the Ajax Bay in the Sea of Japan in the temperate monsoon climate zone. Images of FECP were made by unmanned aerial vehicle (UAV) with additional terrestrial laser scanning (TLS) in 2024. Observed terrain models were classified by types of land usage. Heights of trees were clarified by data from open sources. Preliminary data on biomass content and carbon reserves have been calculated.